Motivational Determination of Professional Self-efficiency of Personality - Krevska, Olha (Psychological Prospects Journal, 2017)
The article is devoted to the empirical substantiation of the motivational factors of professional self-efficacy of personality. It is emphasized that research strategies for the applied study of professional self-efficacy of personality are poorly researched for the specialists of the political sphere of activity. The program of empirical study of the stated problem on the sample of specialists of the political sphere, which are at the stage of professional training and the stage of actual professional implementation is developed. The proposed set of used psychodiagnostic methods and methods of mathematical processing of the results of the study allowed to specify the psychological characteristics of the subjects studied in the form of empirical psychological facts: a motivational determination of professional self-efficacy for specialists with different experience of implementation differs in psychological content of the content. For future specialists, political scientists motivational factors of their self-efficacy are indicators of orientation to the game, constructive motivation of communication and perceptual competence, and for the experts of the political sphere motivational factors of professional self-efficacy are constructive communicative, social adaptation and aspiration to social order. Based on empirically recorded differences, one can justify variants of psycho-correction technologies to support the self-improvement potential and block the signs of professional stagnation of specialists in the political sphere of implementation.